Serum pyruvate and lactate predict immunotherapy efficacy in advanced gastric cancer: a prospective biomarker study - Liu, Chang; Dai, Ying; Wang, Jiru; Wu, Jingjing; Wei, Bin (Frontiers in Immunology, 2025)
BackgroundWhile immunotherapy has redefined clinical paradigms for advanced gastric cancer, reliable efficacy prediction remains a critical unmet challenge. Unlike invasive tissue-based predictors, circulating biomarkers offer non-invasive monitoring potential. This study investigated serum energy metabolites, whose dysregulation drove immune evasion, as predictors of therapeutic efficacy in advanced gastric cancer receiving first-line chemoimmunotherapy.MethodsWe conducted a prospective observational study involving 52 patients with advanced gastric cancer receiving first-line chemoimmunotherapy. Serum metabolites of glycolysis and tricarboxylic acid (TCA) cycle were quantified via high-performance liquid chromatography-tandem mass spectrometry. Therapeutic response, progression-free survival (PFS), and overall survival (OS) were served as evaluation endpoints.ResultsPatients exhibiting decreased serum concentrations of glycolytic metabolites (lactate and pyruvate) demonstrated significantly higher disease control rate (DCR) compared to those with elevated concentrations. Elevated serum lactate and pyruvate were significantly associated with inferior PFS and OS. Multivariate Cox regression established low lactate and pyruvate as independent prognostic factors for improved PFS and OS. However, no significant associations were observed between serum TCA cycle metabolites (citrate, isocitrate, α-ketoglutarate, succinate, fumarate, malate, and oxaloacetate) and DCR, PFS, or OS.ConclusionOur findings suggest that serum lactate and pyruvate as non-invasive glycolytic biomarkers with substantial predictive value for immunotherapy efficacy in advanced gastric cancer, requiring validation in larger cohorts to guide therapeutic decisions.